2020
DOI: 10.1016/j.chaos.2020.110006
|View full text |Cite
|
Sign up to set email alerts
|

A novel mathematics model of covid-19 with fractional derivative. Stability and numerical analysis

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 12 publications
(16 reference statements)
0
36
0
1
Order By: Relevance
“…In other words, how stochastic perturbations affect the deterministic model is described by Eqs. (1)- (8) in this paper. Due to some random environmental effects, for the rest of the paper, we consider the following perturbation terms: we replace in Eq.…”
Section: Description Of the Model Predicting The Novel Coronavirusmentioning
confidence: 73%
See 1 more Smart Citation
“…In other words, how stochastic perturbations affect the deterministic model is described by Eqs. (1)- (8) in this paper. Due to some random environmental effects, for the rest of the paper, we consider the following perturbation terms: we replace in Eq.…”
Section: Description Of the Model Predicting The Novel Coronavirusmentioning
confidence: 73%
“…In [ 7 ], Li et al have proposed the SEIQDR model for predicting the novel coronavirus. In [ 8 ], Alkahtani et al have studied the stability analysis and suggested a numerical scheme for their proposed model. There exist many investigations related to the epidemic models in general [ 9 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, scientists have recently presented some fractional-order mathematical models for COVID-19 (see for example, Atangana [59] , Khan and Atangana [60] , Tuan et al. [61] , Higazy [62] , Alkahtani and Alzaid [63] , Zhang [64] , Yadav and Verma [65] , Baleanu et al. [66] , Mohammad and Trounev [67] , and Zhang and Jain [68] ).…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we propose a new deterministic ODE model, which has four ODEs, for the study of spread and control of infectious disease of COVID-19. COVID-19 is an active research topic not only in the community of mathematical epidemiology group [ 1 , 6 , 9 , 28 , 41 ] but also the problem is of interests in various scientific communities including the group of modeling biological systems [ 13 , 8 ], biomedical engineering [ 33 , 5 ] and signal processing [ 46 ], etc. To prepare a new mathematical model for a specific disease, some population-specific assumptions are important to make the model simple.…”
Section: Introductionmentioning
confidence: 99%